2022
DOI: 10.1371/journal.pone.0265265
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory efficacy of selected synthetic insecticides against second instar invasive fall armyworm, Spodoptera frugiperda (Lepidoptera: Noctuidae) larvae

Abstract: Maize is the most essential crop of China and its productivity has been recently endangered by the fall armyworm (FAW), Spodoptera frugiperda. Chemical pesticides are one of the most important strategies for managing FAW on a short-term basis. The seven synthetic insecticides including novel and conventional belong to four chemical group, spinetoram and spinosad (spinosyns), lambda-cyhalothrin, cypermethrin and bifenthrin (pyrethroids), abamectin (avermectins), broflinilide (diamides), were assessed for their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 59 publications
2
21
0
Order By: Relevance
“…The FAW eggs were established using a collection of larvae that were found on maize crops from Guangdong province, China, during the maize growing season. The collected larvae were cultured on an artificial diet [ 69 ] and the resultant adults were fed artificial diets of a 10% honey solution soaked into sterile cotton balls. The larvae were kept under laboratory conditions at 25 ± 2 °C, with a photoperiod of 12:12 (dark: light) and 65% ± 5% relative humidity (RH).…”
Section: Methodsmentioning
confidence: 99%
“…The FAW eggs were established using a collection of larvae that were found on maize crops from Guangdong province, China, during the maize growing season. The collected larvae were cultured on an artificial diet [ 69 ] and the resultant adults were fed artificial diets of a 10% honey solution soaked into sterile cotton balls. The larvae were kept under laboratory conditions at 25 ± 2 °C, with a photoperiod of 12:12 (dark: light) and 65% ± 5% relative humidity (RH).…”
Section: Methodsmentioning
confidence: 99%
“…The larvae of the pest eat the leaves, stalks, and flowers of cultivated plants [ 1 , 7 ]. The S. frugiperda populations are often controlled using chemical pesticides [ 8 , 9 ]. Different types of insecticides work in different ways to kill the target organisms [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Spinosad has been found as the most effective pesticide with the highest mortality of FAW larva within a very short time as explained by Cook et al (2004). Similar studies have been conducted around the world including China, Africa, Brazil and India to test the efficacy of pesticides in field and laboratory conditions to control FAW, and reported that FAW is susceptible to synthetic pesticides, however, Spinosad, Chlorantraniliprole and Emamectin benzoate causes the highest mortality compared to other synthetic pesticides (Idrees et al, 2022). Continuous application of such pesticides in the field may increase resistance against many categories of pests including FAW (Osae et al, 2022).…”
Section: Resultsmentioning
confidence: 72%